RIPK3-Dependent Necroptosis Limits PRV Replication in PK-15 Cells - Gou, Hongchao; Bian, Zhibiao; Cai, Rujian; Chu, Pinpin; Song, Shuai; Li, Yan; Jiang, Zhiyong; Zhang, Kunli; Yang, Dongxia; Li, Chunling (Frontiers in Microbiology, 2021)
Pigs infected by PRV display necrotic pathology in multiple organs. The mechanism by which PRV induces cell death is still unclear. Recently, necroptosis was identified as a programmed process dependent on the receptor interacting protein kinase 3 (RIPK3) and mixed lineage kinase-like protein (MLKL). In this study, we demonstrated that PRV induced RIPK3-dependent necroptosis in PK-15 cells. The data showed that PRV infection caused cell death with PI-positive staining. Transmission electron microscopy analysis indicated plasma membrane disruption in PRV-infected cells. A pan-caspase inhibitor did not prevent PRV-induced necrotic cell death. Western blot analysis indicated that caspase-3 and caspase-8 were not cleaved during PRV infection. Although the transcription of TNF- was increased by PRV infection, RIPK1 was shown to not be involved in PRV-induced necrotic cell death by use of its specific inhibitor. Further experiments indicated that phosphorylation of RIPK3 and MLKL was upregulated in PRV-infected cells. Stable shRNA knockdown of RIPK3 or MLKL had a recovery effect on PRV-induced necrotic cell death. Meanwhile, viral titers were enhanced in RIPK3 and MLKL knockdown cells. Hence, we concluded that initiation of necroptosis in host cells plays a limiting role in PRV infection. Considering that necroptosis is an inflammatory form of programmed cell death, our data may be beneficial for understanding the necrotic pathology of pigs infected by PRV.